Clinico-Pathological Profile of Hodgkin’s Lymphoma: A Single-Center Study from Nepal - Jha, Ajay Kumar; Shrestha, Prakash; Subedi, Garima (Nepalese Journal of Cancer, 2026)
Background: Hodgkin’s lymphoma (HL) is a highly curable lymphoid malignancy with excellent outcomes when diagnosed early and treated with standardized multimodal therapy. However, data from low- and middle-income countries (LMICs) remain limited and are largely derived from single-center experiences. Objective: To describe the clinico-pathological characteristics, staging, treatment patterns, and outcomes of patients diagnosed with Hodgkin’s lymphoma at a tertiary care center in Nepal. Methods: This retrospective observational study included consecutive patients diagnosed with Hodgkin’s lymphoma at Vayodha Hospital, Nepal, between July 2022 and June 2025. Diagnosis was established using histomorphology and confirmed by immunohistochemistry. Disease staging was performed using contrast enhanced computed tomography (CECT) according to the Ann Arbor staging system. Clinical, pathological, treatment, and outcome data were analyzed descriptively. Results: A total of 35 patients were included. The mean age at diagnosis was 33.3 years (range: 4–74 years), with a predominance of young patients aged 10–30 years (46%). The male-to-female ratio was 1.3:1. Cervical lymphadenopathy was the most common presentation (57%). Mixed cellularity was the predominant histological subtype (68%). Advanced-stage disease (Stage III–IV) was observed in 54% of patients. Majority (89%) patients received chemotherapy, predominantly ABVD. One treatment-related mortality and one relapse were observed during a median follow-up of 36 months. Conclusion: Patients with Hodgkin’s lymphoma in Nepal commonly present at a younger age and with advanced-stage disease. Despite resource limitations, outcomes remain favorable with standard chemotherapy regimens. Strengthening early diagnosis and referral systems may further improve survival outcomes in LMIC settings.